SCHOOL STUDENTS DAY, WEEK, MIDDLE OF THE YEAR STRUCTURE AND RATING - O. S. Jumanov (Galaxy International Interdisciplinary Research Journal, 2022)
Students should be able to accurately assess the workday with workouts that develop or support during physical education and sports, the workday without developmental workouts, and the days off. The annual cycle consists mainly of weekly blocks; with the change of seasons and the weather, physical education, health-improving physical education tools will change, but the loads will remain relatively stable.